4. Alienation and liberation of woman in the church : a treatment of the erotic in theology - Dussel, Enrique D. (Orbis Books, 2021)
My topic is very important for Latin America in general and the church in particular. My topic is woman s place in the church; my problem is how to phrase the question. To pose this question of woman s place in the church, we must begin with the face-to-face, the original experience of Moses who came face-to-face with God. This experience can be described or analyzed on three levels because there are three possible kinds of relationship of person with person (we are reminded here analogically of the three persons of the Trinity). They are male-female, which becomes father-mother, parent-child, and brother-sister. The first is an erotic relationship, the second pedagogical, and the third political. And this applies even to the relationship of the totality of humankind before God, which is humankind s theological position, but always through the mediation of people, through "the poor, the orphan, or the widow ," as the prophets say. Let us now take up the first of these relationships, which even genetically is first.